PENGEMBANGAN MEDIA KOMIK IPA UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN KARAKTER PESERTA DIDIK SMP - Widyawati, Ani; Prodjosantoso, Anti Kolonial (Jurnal Inovasi Pendidikan IPA, 2015)
The objectives of this research were (1) to know the characteristics, (2) to review the advisability, and (3) to find out whether the science comic improve students learning motivation and character. This research is classified to Research and Development (R & D) by referring to the ten main procedures developed by Borg and Gall. However this research only applied nine of the ten procedures stated above, they were: introduction, planning, developing, early try out, revision, limited try out, and final product revision. The subject of this research was grade VIII students of SMP Muhammadiyah 2 Yogyakarta. There were 43 respondents consisting of 5 students for individual try out, 10 students for small group try out, and 28 students for field try out. The data collecting instruments were validation sheet for media and material experts, observation sheet, interview guidelines, and students'character and motivation questionnaire sheet. The result of this research are as follows: (1) the characteristic of science comic were character-based and contained integrated science's material, (2) the advisability of character education-based science comic is considered as very good, and (3) therefore, the comics are applicate to develop motivation and character for JHS students.